Atomically flat superconducting NbN thin films grown on SrTiO3 (111) by plasma-assisted MBE - Guan-Yong Wang; Zhen Zhu; Xin-Yi Yang; Lu Dong; Hai-Yang Ma; Hao-Hua Sun; Ai-Min Li; Dan-Dan Guan; Dong Qian; Canhua Liu; Yao-Yi Li; Jin-Feng Jia (APL Materials, 2017)
Atomically flat superconducting NbN thin films have been grown on the SrTiO3 (111) substrate by plasma-assisted molecular beam epitaxy for the first time. Using scanning tunneling microscopy and in situ reflection high energy electron diffraction, we investigate the surface structure of epitaxial NbN thin films on the SrTiO3 (111) substrate. The orientation [101¯]NbN//[112¯]STO is dominating at substrate temperature above 700 °C. The quality of the as-grown films can be further improved by annealing at elevated temperatures. The homogeneous spatial distribution of superconducting gaps and magnetic vortices further demonstrates the high quality of the NbN films.